Alluvial fan formation near Aklavik, Northwest Territories, Canada - Legget, R. F.; Brown, R. J. E.; Johnston, G. H. (1966)
When the Canadian Government decided to relocate the town of Aklavik in the delta of the Mackenzie River, Northwest Territories, the search for a new site involved detailed site investigations of four prospective locations. One was on the gently sloping surface of an alluvial fan between the Richardson Mountains and the western rim of the Mackenzie Delta. Predictions from surficial evidence and from a detailed study of aerial photographs were invalidated when drilling in the perennially frozen ground disclosed at least 40 feet of organic silt and no sand or gravel as had been expected. The adjacent mountains of Cretaceous age supply materials eroded from sandstone and shales. The action of frost probably induces mechanical disintegration. Turbulent stream flow continues the erosion process, which appears to be still further aided by the annual growth of fast-growing sedges and grasses on the surface of the stream meanders. The short but warm growing season leads to rapid decay of this grass cover; this combined with the annual layers of stream-bed material results in the fans being composed predominantly of organic silt with only minor quantities of coarse-grained material. Lorsque le Gouvernement canadien décida de déplacer la ville d'Aklavik, située dans le delta du fleuve Mackenzie, Territoires du Nord-Ouest, la recherche d'un nouvel emplacement nécessita l'examen approfondi des quatre endroits qui semblaient convenir à cette fin. L'un d'entre eux se situait à la surface d'un cône alluvionnaire en pente douce encadré par les Monts Richardson et la bordure ouest du delta du Mackenzie. On constata que les prévisions basé es sur l'observaton des traits physiques de la surface et sur l'étude détaillée des photographies aériennes étaient erronées lorsque des sondages dans le pergélisol révèlent l' existence d'une couche de tangue d'une épaisseur d'au moins 40 pieds, mais non du sable, ni du gravier qu'on attendait. Les matériaux alluvionnaires proviennent de l'érosion du grè s et du schiste des montagnes adjacentes datant du Crétacé. L'action du gel amorce probablement la désagrégation des roches et le courant tumultueux du torrent continue le processus d'érosion auquel semble contribuer en outre la pousse annuelle du carex et des herbes à croissance rapide sur la surface alluvionnaire située entre les méandres du torrent. La saison de croissance courte mais chaude amène la décomposition rapide de cette couverture herbeuse qui, mê lée aux couches annuelles de matériaux alluvionnaires, constitue des cônes composés principalement de tangue ne comprenant que de faibles quantités de matériaux à granulomé trie grossière. Peer reviewed: No NRC publication: Yes